Trp-574-Leu and the novel Pro-197-His/Leu mutations contribute to penoxsulam resistance in Echinochloa crus-galli (L.) P. Beauv. - Sun, Penglei; Niu, Liangliang; He, Pengfei; Yu, Haiyan; Chen, Jingchao; Cui, Hailan; Li, Xiangju (Frontiers in Plant Science, 2024)
Recently, due to the widespread use of the acetolactate synthase (ALS)-inhibiting herbicide penoxsulam in paddy fields in China, Echinochloa crus-galli (L.) P. Beauv. has become a problematic grass weed that is frequently not controlled, posing a threat to weed management and rice yield. There are many reports on target-site mutations of ALS inhibiting herbicides, however, the detailed penoxsulam resistance mechanism in E. crus-galli remains to be determined.Greenhouse and laboratory studies were conducted to characterize target-site resistance mechanisms in JL-R, AH-R, and HLJ-R suspected resistant populations of E. crus-galli survived the fieldrecommended dose of penoxsulam. The whole-plant dose-response testing of E. crus-galli to penoxsulam confirmed the evolution of moderate-level resistance in two populations, JL-R (9.88fold) and HLJ-R (8.66-fold), and a high-level resistance in AH-R (59.71-fold) population. ALS gene sequencing identified specific mutations in resistant populations, including Pro-197-His in ALS1 for JL-R, Trp-574-Leu in ALS1 for AH-R, and Pro-197-Leu in ALS2 for HLJ-R. In vitro ALS activity assays demonstrated a significantly higher activity in AH-R compared to the susceptible population (YN-S). Molecular docking studies revealed that Trp-574-Leu mutation primarily reduced the enzyme's ability to bind to the triazole-pyrimidine ring of penoxsulam due to decreased π-π stacking interactions, while Pro-197-His/Leu mutations impaired binding to the benzene ring by altering hydrogen bonds and hydrophobic interactions. Additionally, the Pro-197-His/Leu amino acid residue changes resulted in alterations in the shape of the active channel, impeding the efficient entry of penoxsulam into the binding site in the ALS protein. The three mutant ALS proteins expressed via the Bac-to-Bac baculovirus system exhibited notably lower activity inhibition rates than the non-mutant ALS proteins to penoxsulam, indicating all three ALS mutations reduce sensitivity to penoxsulam. This study elucidated the distinct impacts of the Pro-197-His/Leu and Trp-574-Leu mutations in E. crus-galli to penoxsulam resistance. Notably, the Trp-574-Leu mutation conferred stronger resistance to penoxsulam compared to the Pro-197-His/Leu mutations in E. crus-galli. The Pro-197-His/Leu mutations were first detected in E. crus-galli conferring penoxsulam resistance. These findings provide deeper insights into the molecular mechanisms underlying target-site resistance to penoxsulam in E. crus-galli.